2020
DOI: 10.1080/02656736.2020.1803424
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of curative treatment for colorectal liver metastases combined with cytoreductive surgery and intraperitoneal chemotherapy for peritoneal metastases: a systematic review and meta-analysis of current evidence

Abstract: View related articles View Crossmark data Clinical outcomes of curative treatment for colorectal liver metastases combined with cytoreductive surgery and intraperitoneal chemotherapy for peritoneal metastases: a systematic review and meta-analysis of current evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…In a recent meta-analysis, the median OS for CRAdenoCa peritonectomy patients without sLM ranged from 21 to 65 months, which is approximately consistent with the median OS of 20 months for this cohort in our study (15). For AAdenoCa patients without sLM, no specific survival studies have been performed.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent meta-analysis, the median OS for CRAdenoCa peritonectomy patients without sLM ranged from 21 to 65 months, which is approximately consistent with the median OS of 20 months for this cohort in our study (15). For AAdenoCa patients without sLM, no specific survival studies have been performed.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the feasibility and safety of the combined LR and CRS–HIPEC in metastatic CRC reported from several studies ( 20 , 22 , 23 , 27 , 33 , 36 , 37 , 39 , 45 ), data on the matter show conflicting results, with updated studies and meta-analyses demonstrating evidence to the contrary ( 5 , 21 , 32 , 34 , 46 ). Razenberg et al ( 47 ) reported a significantly lower median OS in patients with concomitant PC + LM treated with palliative chemotherapy compared to the patients treated with CRS and HIPEC (12.5 vs. 23.1 months). However, there could be a biased selection in interpreting this result as no data regarding the two groups (dissemination of the disease, history prior to treatment, and general conditions of the patients) were available.…”
Section: Discussionmentioning
confidence: 99%